From eruption to construction - Part B: Investigating the feasibility of volcanic material as partial replacement for cement in concrete - Eklund, Victor; Andersson, Matilda; Jonsson Agnes; Dahl, Clara; Olsson, Lukas; Jakobsson Yasmine (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik (ACE), 2024)
This study investigates to what extent supplementary cementitious materials, (SCMs) of volcanic material (VM) together with limestone (LS) can replace ordinary Portland cement, (OPC) in concrete through an experimental study. The study is done in collaboration with a partner group named Part A. They are conducting a similar study in which part SCM is replaced only with VM. The project is thus divided into two parts, with this study being part B. Nine mortar mixtures were tested for compressive strength, with an accompanying X-ray diffraction (XRD) analysis of pastes, to assess chemical properties over time. Out of the nine mixtures, one contains 100% OPC and is referred to as the reference mix (REF). Additionally, there are four mixtures with varying proportions of VM and LS, and four filler mixtures with corresponding amounts of filler to the VM-LS mixtures. Furthermore, a thorough explanation of key materials and concepts is done to provide enough information for sufficient understanding. A detailed description of methods is provided and specific information on each material used, such as Icelandic hyaloclastite from Grindavik and limestone from Cementa, Sweden. Compressive strength tests were performed to evaluate the strength properties of each mixture relative to a reference mix (REF). Through these results, the optimal ratio of VM and LS to OPC can be concluded. This study showed that the mixture substituted with 40% SCM composed of 30% VM and 10% LS provided the highest strength properties and was comparable to the reference mixture of 100 percent OPC. Therefore, this study concluded that hyaloclastite and limestone can replace 40% of OPC in concrete.